Effect of packing density of lipid vesicles on the Aβ42 fibril polymorphism. (May 2021) - Heo, Chae Eun; Park, Chae Ri; Kim, Hugh I.
Graphical abstract: Highlights: The differences in packing density of lipids modulates Aβ42 fibrillations. Membranes with low packing density enhance Aβ42 fibrillations and shorten fibrils more than tightly packed membranes. Anionic lipids impede Aβ42 fibrillations due to tight binding of Aβ42 to the membrane surface via electrostatic interactions. Hydrophobic and electrostatic interactions between lipids and proteins are crucial in lipid-related amyloid fibrillations. Abstract: The aggregation of amyloid-β 1–42 (Aβ42) on lipid membranes is closely related to the pathology of Alzheimer's disease (AD). Herein, we demonstrated the effect of the packing density of lipid vesicles on the Aβ42 fibrillation kinetics and fibril morphology. We used three distinct phosphatidylcholine (PC) lipids, containing different numbers of cis -double bonds in acyl chains, and therefore, a different packing density in the lipid vesicles. Our results showed that the fibrillation of Aβ42 was greatly enhanced and the formed fibrils became shorter as the number of double bonds in lipids increased. Due to the low-density characteristics of dioleoyl phosphatidylcholine (DOPC), Aβ42 monomers were able to interact with the hydrophobic acyl chain of lipids exposed to the aqueous phase, thereby inducing rapid fibrillation and short fibril morphologies. Furthermore, the effects of the anionic lipids dioleoyl phosphatidylserine (DOPS) and dioleoyl phosphatidylglycerol (DOPG), and mixed vesicles of DOPC/DOPS and DOPC/DOPG on Aβ42 fibrillations were investigated. The tight binding of Aβ42 to the lipid head groups via electrostatic interactions was able to suppress the modulation of Aβ42 fibrillations compared to accelerated fibrillations on loosely packed membranes. Our proposed mechanism regarding the influence of lipid packing density on Aβ42 fibrillations provides an advanced understanding of lipid-associated amyloid fibrillations.